(untitled) (Minerva, 2019)
This paper provides two new fragments of Epicharmus that had hitherto passed unnoticed to the editors of this author. Both fragments are quoted by ancient writers. One of them comes from Athenaeus and contains a statement, according to which Epicharmus was the first comedy-writer to bring a drunkard on the stage. The second fragment comes from the Latin work Explanationes in artem Donati, and it contains the word used by Epicharmus to name the circumflex accent. Whether the latter fragment belongs to a comedy by Epicharmus or to one of the spurious poems attributed to him is uncertain.